S-task simulation builder framework as preventive work risk analysis - Pande Ketut Sudiarta; Made Sudarma; Rukmi Sari Hartati; Ida Bagus Alit Swamardika (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
Computer methods in biomechanics are computer methods for solving biomechanics problems. Rula, Reba, Niosh, Owas is a method of analyzing work risks due to incorrect posture. Each method uses a worksheet on one posture to analyze risk. For dynamic work, a computer method is needed that can quickly calculate every change in posture. Virtual reality and Kinect as dynamic work analysis methods cannot be carried out preventively. Preventive measures are needed to prevent workers from risks resulting from work. For this reason, computer simulation methods are needed to create work stations and work processes so that they can be carried out preventively. The s-task simulation builder (S-TSB) framework provides a dynamic work analysis solution using simulation. The three processes carried out include surveying, creating simulations and processing posture data. Software validation was tested using the black box analysis method and the results were as expected. The dynamic working model is tested showing results in the form of graphs so it is easy to compare each change. The use of simulation also saves design costs because optimization can simply be done by changing the simulated work station data and/or work process.